Kepimpinan Kepala Sekolah dalam Pengembangan Pembelajaran PAI di SMP Islam Terpadu Misykat Al Anwar Kwaron Diwek Jombang - Nurul Indana; Fitriatul Jannah; Noor Fatikah (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2019)
Head master role is very important, they have to be able to plan, conduct, and evaluate their programs periodically towards education process. Learning as interactive process between students and their environment, so the practice is more important. The role of PAI in school is for founding Indonesia young generation especially in creating good and faithful human. The research result are: 1). the head master observes directly when the learning process occured, involved his vice especially for kepondokan task, asks the teachers to join workshop, PAI is taught integrally, adding reading and writing al qur’an as mulok, reading kitab, praying practice, and another extra program. 2). The lesson plan including discussion, demostration as method, it uses national curriculum, learning sometimes is done out of class, and PAI is developed through bulughul al- maram and adabu at ta’lim wa al muta’allim, evaluation is conducted oral and written test. The supporting factors are professional teachers, good facilities, and most of students stay in Islamic boarding schools. The various students capability, and the limited time given are as obstacles factor.